The effect on emergency department visits of raised alcohol minimum prices in Saskatchewan, Canada. (12th February 2018) - Sherk, Adam; Stockwell, Tim; Callaghan, Russell C.
Abstract: Introduction and Aims: The province of Saskatchewan, Canada introduced minimum prices graded by alcohol strength in April 2010. As previous research found this intervention significantly decreased alcohol consumption and alcohol‐attributable morbidity, we aim to test the association between the intervention and the rate of emergency department (ED) visits in four alcohol‐related injury categories [motor vehicle collisions (MVC), assaults, falls and total alcohol‐related injuries]. Design and Methods: Data on ED visits in the city of Regina were obtained from the Saskatchewan Ministry of Health. Auto‐regressive integrated moving average time series models were used to test the immediate and lagged effects of the pricing intervention on rates of alcohol‐related nighttime. ED visits and controlled for daytime rates of ED visits, economic variables, linear and seasonal trends, and auto‐regressive and moving average effects. Results: The implementation of an alcohol minimum pricing strategy in Saskatchewan was associated with decreased MVC‐related ED visits for women aged 26 and over after a 6 month lag period (−39.4%, P  < 0.001). There was no significant abrupt effect of this intervention on ED visits of four injury types in any of four gender‐age categories; however, rates of ED visits among young males for MVCs and assaults decreased substantially during this study. Discussion and Conclusions: The minimum pricing policy change led to a lagged decrease in motor vehicle‐collision‐related ED visits for women older than 25. Of note, there did not appear to be an instantaneous effect on the rate of alcohol‐related injury ED visits immediately after the policy implementation nor lagged effects for other gender‐age groups.